“Desarrollo financiero y crecimiento económico: Un análisis con datos de panel para 16 países de América Latina, período 1988-2018” - Medina Alvarado, Johanna Patricia (2021)
Low economic growth is one of the most serious problems facing Latin American countries, taking into account that their growth averaged 0.3% during the 2014-2019 period (Economic Commission for Latin America and the Caribbean (ECLAC, 2021)). That is why this research aims to determine the effect of financial development on economic growth for 16 Latin American countries, using econometric panel data techniques, period 1988-2018. Use statistical information collected by the World Development databases Indicators (WDI, 2020) and Penn Word Table (PWT, 2019), considering GDP per capita as a measure of economic growth as a dependent variable, domestic credit to the private sector as a proxy for financial development and as control variables: consumption of non-renewable energy, renewable energy consumption and human capital. In addition, second-generation econometric techniques were used in the presence of cross-sectional dependence, first the Westerlund test (2007) was applied together with the Fully Modified Ordinary Least Squares (FMOLS) and the Granger causality developed by Dumitrescu and Hurlin (2012). The results indicate that there is a long- term equilibrium relationship between the variables. Likewise, it is found that a higher level of financial development leads to greater long-term economic growth. Finally, the existence of bidirectional causality between financial development and economic growth was determined. Given this, the policy implications derived from this research should be focused on innovation and expansion of financial services.